A decade of interdiction and disqualification: comparision of interdiction/disqualification action proceedings between two triennia - Santos, Telma; Alcafache, João; Colón, Máximo Fernandez (Sociedade Portuguesa de Psiquiatria e Psicologia da Justiça, 2019)
Introduction: In light of a changing society, from a judicial/legal standpoint, there is an increase of interdiction/disqualification actions which, despite their greater intention to protect unable adults, unequivocally condition individual freedom. As a result, attention to the psychiatric-forensic evolutionary trajectory of interdiction/disqualification is a practice that must compromise any society, as it is very useful for the clinical-forensic system. Objective: To assess and compare the sociodemographic and psychiatricforensic characteristics of interdiction/disqualification proceedings within the scope of Civil Law, between the data of the triennia (T.) from 2014-2016 and of the T. 2005-2007, conducted in the Clinical Forensics Functional Unit of the Center Delegation of the National Institute of Legal Medicine and Forensic Sciences (INMLCF). Material and methods: Comparative statistical analysis of data, on a total of 536 cases. Results: The universe of the population under study for the T. 2014-16 (N= 410), when compared to that of the previous triennium (N=126), evidences a very steep increase in the number of cases. Discussion: The estimated data highlight an effective consistency of the comparative assessment between the triennia, with regard to the majority of sociodemographic categories and psychiatric-forensic variables. There is, however, a percentage expansion regarding the number of proceedings within this scope which, as expected by the authors, seems to be the result of an increase of neurodegenerative pathologies. Conclusions: The audit conducted and the high prevalence of these kinds of proceedings reflect a demanding and concerned society, but also require a judicial/medical-forensic reflection on the challenges of an evolving society.
Santos T, Alcafache J, Colón M. A decade of interdiction and disqualification: comparision of interdiction/disqualification action proceedings between two triennia. Psiquiatria, Psicologia & Justiça. 2019; 15: 86-98.
Keywords: Interdiction; Disqualification; Forensic Psychiatry